Poklicne izkušnje učiteljev in značilnosti pouka v osnovni šoli - Javornik Krečič, Marija (Sodobna pedagogika, 2006)
The purpose of the article is to present teachers' behaviour in class with regard to their professional experience. The data were collected through survey questionnaires in which pupils assessed the behaviour of their teachers in 'mother tongue' classes. The study was conceived on the basis of the cognitive understanding of the profession and the teacher's development (Berliner's model). Cognitive development means a sequence of cognitive structures following each other from the less complex to the more complex. Teachers at higher cognitive levels are believed to have more complex cognitive structures, a wider range of teaching skills, a greater capacity for empathy and insight into problems in a wider context, while they are also considered to perform better in stress situations. We therefore expected that teachers with greater experience would encourage the so-called transformative model of education through their behaviour in the class.
Keywords: vzgoja in izobraževanje; pedagoško delo; učitelji; strokovna usposobljenost; poučevanje